Comparative analysis of technologies and devices for the blind and visually impaired (Texas Journal of Engineering and Technology, 2022)
Today, techniques, technologies, in a word, information technologies are rapidly developing. So far, the development of information technologies and achievements requires the need to inform all spheres of human life. Using the capabilities of these technologies, special devices are produced for blind and visually impaired people. The ability to see, to be able to see fully, understand and perceive this bright world and its diversity is one of the greatest gifts given to mankind. In this paper, we present a general description of devices and technologies for the blind and visually impaired, their principles of operation, as well as a comparative analysis of the results obtained during the research.